Draft Annual Plan 2005-06 Government of Punjab - Planning Commission (Planning Commission, 2005)
Punjab, is a predominantly an agricultural or rural economy. the share of agriculture, as a percentage of Net State Domestic Product for 2002-03, (Q) is 24.82% at constant (1993-94) prices. As per 2001 census,, about 66% of the population resides in rural areas, of which about 80% is still dependent on agriculture and allied activities. Therefore, the major thrust in the plan exercise is needed mainly on agriculture and rural areas. However, a distinct trend towards Industrialization and growth of the services sector in many parts of the state is a reflection of the current global trends. Punjab, is no exception to this process of shift in economy in the quest for achieving higher growth rates.
Government of Punjab, Department of Planning